Hubungan antara Tingkat Kedisiplinan Siswa dengan Hasil Belajar pada Mata Pelajaran Pendidikan Kewarganegaraan - Talakua, Yani; Diawaitouw, Yohana Hulda (CV. Creative Tugu Pena, 2022)
Various efforts are made by every education manager to obtain the quality and quantity of education in order to improve student learning achievement. One of the steps taken is to increase student discipline. The article analze the correlation of . This research type is quantitative research. It take primary data sources, namely all students of class X in Stae Senior High School (SMA) Negeri Samber, with 60 sample of students. The researchers used questionnaire in collecting data, to obtain data on variable X, namely the level of student discipline. Furtermore, documentation to obtain data for variable Y, namely learning outcomes in civic education subjects for class X students at SMA Negeri Samber. Analyzing data uses product moment analysis. The result show that learning outcomes in the subject of civics education, from the r xy = 0.652 test and obtained t count = 6.605. Then, the tcount value is consulted against the ttable value at a The significance level of 0.05 = 1.684. Based on this value, it can be explained that t count and t table means; Ha is accepted and Ho is rejected. Hence, there is a significant relationship between student discipline and learning outcomes for civic education subjects for class X students at SMA Negeri Samber. Keywords: Learning Outcome, Students’ Dicipline, Dicipline Learning